Diversity, Occurrence And Development Of Forensic Insects On Dog Canis Domesticus L. Carcass From Kolhapur, India. - JADAV DIVYA K.; T.V. SATHE (International Journal of Pharma and Bio Sciences, 2015)
Kolhapur region, India is characterized by a very rich biodiversity since it receives 700mm-6000mm rainfall and contains several water bodies and forestry including Western Ghats, one of the hot spots of biodiversity conservation and protection. Insects play a very crucial role in forensic science for solving the problems related to murder, suicide, sexual molestation, child- neglect and abuse, etc. The hosts of forensic insects may be various vertebrates such as amphibians, reptiles, birds and mammals including humans. Therefore, diversity of forensic insects on Canis domesticus L. carcasses from Kolhapur, India has been reported. A total of 11 species including flesh flies (2), blow flies (3) and beetles (6) have been found associated with the carcasses of dog in Kolhapur. The flesh flies and blow flies occurred on moist corpse, silphid beetles occurred on active decomposition stage and dermestids and clerids occurred on advanced stages of carcasses. The flesh flies developed from egg to adult within 13-15 days while blow flies completed their life cycle within 7- 19 days. The development time from egg to adult for beetles ranged from 8.5 to 18 days (table-2).